Development Of National Legal Political Strategy In Indonesia - Damayanti, Amalia Chrisna; Permata Sari, Diah Ayu; Husain, Hamzir; Al Ghiffari, Salman (KnE Social Sciences, 2024)
In the development of the political situation entering the era of the third millennium, in various countries, it turned out that they were leaving political autocracies that were more dynamic toward legal reform, including Indonesia, which had implications for amendments to the 1945 Constitution. The study aimed to analyze the problem, how to correlate legal reform with the development of national legal politics in Indonesia. The study method used was descriptive analysis approach. The discussion of these problems that correlate legal reform in the development of national legal politics in Indonesia, in essence, has a philosophical content to achieve legal goals within the framework of realizing the goals of the Indonesian state, namely achieving a just and prosperous society. It can be concluded that the development of national legal politics is one of the important areas of development, which also requires intensive attention and handling like other development fields. In the transitional era of the New Order era to the Reformation era, national law reforms provided accommodation to resolve various problems. The political development of the national law seems rather difficult to implement so that in some ways the politics of national law development seems to be somewhat sloganistic. Keywords: development of national, legal political, Indonesia